INOVASI TEKNOLOGI PENDIDIKAN - Rini Sabrina; Wawan Hendrawan; Yuly Suryandari; Lukman Nulhakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Basically, the learning process is an organized and structured method to archieve the intended goals and ensure that fundamental abilities are attained with satisfactory outcomes. Therefore, to ensure that students gain meaningful and successful learning experiences, a professional teacher must possess the ability to generate new ideas and adapt them. The success of learning is greatly influenced by the application of innovative technology in suitable and effective teaching practices. Educational technology involves research and implementation in the development, application, and management of reliable technology to support learning and enhance learning outcomes. Innovation never ceases due to the courage to take action. Innovation is required in all fields, including technology. This occurs at all stages of the education system and at every level within the educational structure.